2017
DOI: 10.1038/mp.2017.191
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes exacerbates maternal immune activation effects in the developing brain

Abstract: Maternal inflammation and diabetes increase the risk for psychiatric disorders in offspring. We hypothesized that these co-occurring risk factors may potentiate each other. To test this, we maternally exposed developing mice in utero to gestational diabetes mellitus (GDM) and/or maternal immune activation (MIA). Fetal mouse brains were exposed to either vehicle, GDM, MIA or GDM+MIA. At gestational day (GD) 12.5, GDM produced a hyperglycemic, hyperleptinemic maternal state, whereas MIA produced significant incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 85 publications
3
58
0
3
Order By: Relevance
“…Moreover, hyperglycemia and hyperinsulinemia, situations produced during diabetes, can increase systemic inflammation and exaggerate and/or prolong responsiveness to pro-inflammatory stimuli, supporting a possible interaction of GDM and MIA. These data suggest that children born to mothers with GDM, exposed to midgestation infections/immune activation, have increased vulnerability for developmental disorders [78].…”
Section: Inflammation Underlying Gdm Development and Derived Adverse mentioning
confidence: 81%
“…Moreover, hyperglycemia and hyperinsulinemia, situations produced during diabetes, can increase systemic inflammation and exaggerate and/or prolong responsiveness to pro-inflammatory stimuli, supporting a possible interaction of GDM and MIA. These data suggest that children born to mothers with GDM, exposed to midgestation infections/immune activation, have increased vulnerability for developmental disorders [78].…”
Section: Inflammation Underlying Gdm Development and Derived Adverse mentioning
confidence: 81%
“…In these MIA TAC mice, increased maternal IL-6 acts to stimulate the secretion of IL-17a from maternal T helper (Th) 17 cells, which is necessary and sufficient to cause aberrant behaviors in offspring (12). While this study did not find MIA phenotypes in offspring from SFB-negative JAX dams, mice from JAX have been used successfully as MIA models in previous reports (6,9,23,32,33). In order to determine whether SFB and IL-17a are required in the generation of MIA outcomes, we first confirmed that C57/B6 mice purchased from TAC harbor SFB while those from JAX do not and we found that CR mice have levels of SFB comparable to TAC mice (Supplemental Fig.…”
Section: Mia Engages Distinct Molecular Pathways In C57/b6 Mice From mentioning
confidence: 56%
“…Furthermore, she carried the diagnosis of gestational diabetes mellitus (GDM). While isolated GDM has not been shown to have the same immunosuppressive effects as longstanding hyperglycemia associated with uncontrolled diabetes, it has been found to heighten systemic inflammation and intensify the body's response to proinflammatory stimuli such as infection [5]. The patient was also pregnant which creates a unique environment for infection.…”
Section: Discussionmentioning
confidence: 99%